Computing [Technology 2000 analysis and forecast]. - Comerford, R. (IEEE spectrum)
The dawning of this millennium coincides with the start of a new epoch-that of Internet-distributed computing-and, as is typical with epochal changes, the entrenched are being uprooted. A new breed of device-the Internet appliance-is dethroning the PC, which has held sway over the computing industry for the last two decades. Microsoft Inc., the Redmond, Wash., software megalith whose Windows operating system has towered over the system software arena for the last decade, must now do battle on two fronts: at the heart of the network-the server-and at the edges, with the new Internet devices. As the number and size of Web publishers mushroom, so does the demand for servers and storage. Sales of server hardware and operating systems are growing rapidly, and Microsoft 2000, formerly known as Windows NT 5.0, must duke it out with established Unix systems and new Linux boxes. With growing reliance on the Internet for all kinds of information, computing is acquiring an unsuspected mobility. Unlike a laptop computer, which requires that the user be stationary (preferably seated) to be of use, Internet appliances free the user to work on the go, in ways not previously possible. Even as information technology reaches the next stage in its evolution, the PC has become something of a dinosaur, a metamorphosis that cannot be stopped even by Microsoft. In fact, while the outcome of its confrontation with the US Department of Justice may be to reshape the company in some way, it is the Internet that is truly restructuring Microsoft